Role of tRNA-Derived Fragments in Protozoan Parasite Biology - Manu Sharma; Upinder Singh (Cells)
tRNA molecules are among the most fundamental and evolutionarily conserved RNA types, primarily facilitating the translation of genetic information from mRNA into proteins. Beyond their canonical role as adaptor molecules during protein synthesis, tRNAs have evolved to perform additional functions. One such non-canonical role for tRNAs is through the generation of tRNA-derived fragments via specific cleavage processes. These tRNA-derived small RNAs (tsRNAs) are present across all three domains of life, including in protozoan parasites. They are formed through the cleavage of the parent tRNA molecules at different sites, resulting in either tRNA halves or smaller fragments. The precise mechanisms underlying the synthesis of various tRNA-derived fragments, including the specific RNases involved, as well as their distinct functions and roles in parasite physiology, are not yet fully understood and remain an active area of ongoing research. However, their role in modulating gene expression, particularly during stress responses, is becoming increasingly evident. In this context, we discuss recent findings on the roles of tRNA-derived small RNA in various protozoan parasites. Furthermore, we investigate how these tsRNAs either modulate gene expression within the parasite itself or are packaged into extracellular vesicles to alter host gene expression, thereby promoting parasite survival and adaptation.